ETOS KERJA DAN PRODUKTIVITAS PETANI SAYUR DI KECAMATAN PAUH KOTA PADANG SUMATERA BARAT - Dhea Fatika Sari; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study will test and analyze the relationship between work ethic and the productivity of vegetable growers in Pauh District, Padang, West Sumatra. This area has a very high potential for vegetable cultivation, with an area of 181 hectares. There are no fewer than 468 farmers who grow different types of vegetables. To get the right research results, the authors used a descriptive quantitative method with a total sample of 47 people and conducted a correlation test using the SPSS program. Based on the correlation test conducted, it was found that the relationship (correlation) between work ethic and the productivity of vegetable growers was 0.698 and included in the strong category. These results also prove that the Ha hypothesis can be accepted with the statement